PENGARUH PENERAPAN KONSEP NEW PUBLIC MANAGEMENT TERHADAP PENINGKATAN KINERJA ORGANISASI - Wardhani, Putri Aunillah; Riharjo, Ikhsan Budi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The concept of New Public Management (NPM) in this research has been represented by four variables with clear and measurable objectives, decentralization, incentive, and performance measurement system. Therefore, this research is meant to examine the influence of the implementation of clear and measurable objectives, decentralization, incentive, and performance measurement system to the enhancement of the organization performance. The sample collection technique has been done by using purposive sampling. The samples from these criteria are respondents who have position as the head of section (echelon functionary 2, 3, and 4). Eighty the head section from eight Kantor Pajak (KPP) Pratama Pelayanan in the area of Surabaya have been obtained as samples from these criteria. The result of the research shows that the clear and measurable objectives, decentralization, and incentive variables do not have any influence to the enhancement of organization performance. Meanwhile, the performance measurement system variable has influence to the enhancement of organization performance.Keywords: new public management, clear and measurable objectives, decentralization, incentive, system of performance measurement system